Dostojanstvo kot temelj pravilnega razumevanja ustavnopravnega koncepta prepovedi diskriminacije glede na starost - Brezovar, Nejc (Pravnik, 2017)
The author argues that in practice the prevailing concept of understanding and interpreting age discrimination is the constitutional law concept, as opposed to the labour law concept. Age is a sui generis prohibited ground with specific characteristics - at the same time age is a static, dynamic, and flexible personal characteristic. We can differentiate between the actual, concrete, and supposed age of an individual, their relative age (age gap), etc. The Supreme Court of Canada often emphasizes that age distinctions are frequently upheld by different courts, since they are still understood as a common and necessary way of ordering our society. They are used to determine when we can marry, vote, drive, consent to sexual intercourse, or sell property etc. Article%s attempt is to contribute to a modern, constitutional, and human rights-based approach understanding of the prohibition of age discrimination. Respect for the inherent dignity of an individual requires an individual assessment of his experience, capabilities, and nothing else. Anything else presents a violation of human dignity for a certain group that is based on supposed incompetence, instead of the factual competence of these persons and is unacceptable in the view of the constitutional concept of prohibiting age discrimination.
Keywords: človekovo dostojanstvo; diskriminacija; starost